Identifying The English Language Need of Vocational High School Students Through The Perspective of Need Analysis - Moh. Arif Mahbub (Jurnal Educazione : Jurnal Pendidikan, Pembelajaran dan Bimbingan dan konseling, 2018)
Adapting the theory of Need Analysis as proposed by Dudley-Evans and St. John (1998), this present study explores the vocational students’ perceptions on their English language needs. Therefore, a descriptive survey was employed. One English teacher and the thirty-two students of SMK Asrama Pembina Masyarakat, Class XI, computer engineering and network (TKJ) program were voluntarily involved in this present study as research participants. The data with regard to the students’ subjective needs were gathered through questionnaire. Semi-structured interview was employed to record the data related to the English teachers’ perception toward the needs of research participants. The findings revealed there had been so many different perceptions with regard to the students’ needs. Moreover, this present study also discussed pedagogical implication on teaching-learning practices. Keywords: Need Analysis; Target Situation Analysis (TSA); Learning Situation Analysis (LSA); Present Situation Analysis (PSA).